Analisis Kesetaraan Gender Dalam Bangku Legislatif Menilik Pada Pengarustamaan Gender (PUG) Di Kabupaten Karawang - Fahra Fajrin Nasta; Indra Aditya (Jurnal Ilmiah Wahana Pendidikan, 2022)
Gender Equality in the field of Legislative Representation is a discussion that still has gender gap problems in it. This research discusses the lack of women's participation in the legislative institutions of Karawang Regency, there is no movement of women's legislatures in women's rights and problems, community culture that still hinders the creation of equality for women. in the legislative field, then the role of the government and the problem of gaps in the quota of seats in the legislature by looking at the Gender Mainstreaming (PUG) program. So that it aims to find out the results of these problems and the solutions that need to be confirmed by the Harvard Gender Analysis method. This research uses descriptive qualitative method prioritizing secondary data with literature study techniques.